Complementary Medicines Used in Ulcerative Colitis and Unintended Interactions With Cytochrome P450-Dependent Drug-Metabolizing Enzymes - Sen, Alaattin (Tubitak Scientific & Technological Research Council Turkey, 2022)
Ulcerative colitis (UC) is an idiopathic, chronic inflammatory disease with multiple genetic and a variety of environmental risk factors. Although current drugs significantly aid in controlling the disease, many people have led to the application of complementary therapies due to the common belief that they are natural and safe, as well as due to the consideration of the side effect of current drugs. Curcumin, cannabinoids, wheatgrass, Boswellia, wormwood and Aloe vera are among the most commonly used complementary medicines in UC. However, these treatments may have adverse and toxic effects due to unintended interactions with drugs or drug-metabolizing enzymes such as cytochrome P450s; thus, being ignorant of these interactions might cause deleterious effects with severe consequences. In addition, the lack of complete and controlled long-term studies with the use of these complementary medicines regarding drug metabolism pose additional risk and unsafety. Thus, this review aims to give an overview of the potential interactions of drug-metabolizing enzymes with the complementary botanical medicines used in UC, drawing attention to possible adverse effects.
Sen, Alaattin/0000-0002-8444-376X;
Keywords: Cytochrome P450; Cyps; Ulcerative Colitis; Complementary Medicines; Herbal Products; Adverse Effect; Tamamlayıcı Ve Entegre Tıp